2017
DOI: 10.1186/s12885-017-3863-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of genes associated with breast cancer cell motility in response to Artemisinin treatment

Abstract: BackgroundWell-known anti-malarial drug artemisinin exhibits potent anti-cancerous activities. In-vivo and in-vitro studies showed its anti-tumor and immunomodulatory properties signifying it as a potent drug candidate for study. The studies of mechanisms of cell movement are relevant which can be understood by knowing the involvement of genes in an effect of a drug. Although cytotoxicity and anti-proliferative activity of artemisinin is evident, the genes participating in its anti-migratory and reduced invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 86 publications
(48 reference statements)
2
19
0
Order By: Relevance
“…ART inhibits cell proliferation, migration and invasion, and induces apoptosis in human breast cancer MCF-7 cells [193,196], while DHA suppresses cell growth through cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells and HepG2 xenograft mice [178]. Similarly, ART induces apoptosis in murine mastocytome P815 cells and hamster kidney adenocarcinoma BSR cells, and inhibits tumor growth in P815 xenograft mice [177].…”
Section: Artemisininsmentioning
confidence: 99%
See 3 more Smart Citations
“…ART inhibits cell proliferation, migration and invasion, and induces apoptosis in human breast cancer MCF-7 cells [193,196], while DHA suppresses cell growth through cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells and HepG2 xenograft mice [178]. Similarly, ART induces apoptosis in murine mastocytome P815 cells and hamster kidney adenocarcinoma BSR cells, and inhibits tumor growth in P815 xenograft mice [177].…”
Section: Artemisininsmentioning
confidence: 99%
“…In the past decades, studies have been focused on studying the anti-cancer mechanisms of ARTs, but there are contentions. ARTs inhibit cancer cell proliferation mainly by the induction of apoptosis through mitochondrialdependent pathways [196,205,206]. ART mediates the release of cytochrome c and caspase-9 cleavage, leading to increased apoptosis in human breast cancer MCF-7 cells [196].…”
Section: Artemisininsmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Previous studies have reported extensive examinations of ARS and its analogs in ovarian, prostate, pancreatic, breast and liver cancers or cells and showed little cytotoxicity and strong synergistic anticancer effects when combined with conventional chemotherapeutic agents. 8,[11][12][13][14] In this study, we investigated the antitumor effects of DHA, one of the analogs of ARS, on the cell proliferation and inhibition of ovarian cancer cells. We also examined the alterations in cellular molecules such as proteins, lipids and nucleic acids using Fourier transform infrared (FTIR) spectroscopy after DHA exposure.…”
Section: Introductionmentioning
confidence: 99%